Digitalization of Battery Manufacturing: Current Status, Challenges, and Opportunities. Issue 17 (9th December 2021) - Ayerbe, Elixabete; Berecibar, Maitane; Clark, Simon; Franco, Alejandro A.; Ruhland, Janna
Abstract: As the world races to respond to the diverse and expanding demands for electrochemical energy storage solutions, lithium‐ion batteries (LIBs) remain the most advanced technology in the battery ecosystem. Even as unprecedented demand for state‐of‐the‐art batteries drives gigascale production around the world, there are increasing calls for next‐generation batteries that are safer, more affordable, and energy‐dense. These trends motivate the intense pursuit of battery manufacturing processes that are cost effective, scalable, and sustainable. The digital transformation of battery manufacturing plants can help meet these needs. This review provides a detailed discussion of the current and near‐term developments for the digitalization of the battery cell manufacturing chain and presents future perspectives in this field. Current modelling approaches are reviewed, and a discussion is presented on how these elements can be combined with data acquisition instruments and communication protocols in a framework for building a digital twin of the battery manufacturing chain. The challenges and emerging techniques provided here is expected to give scientists and engineers from both industry and academia a guide toward more intelligent and interconnected battery manufacturing processes in the future. Abstract : This review is focused on the current and near‐term developments for the digitalization of the lithium‐ion battery (LIB) cell manufacturing chain. Current modelling approaches are reviewed and the main challenges and opportunities to be addressed to further advance in the digital transformation are discussed, including modelling, interoperability, ontology, and usage of protocols, among other issues.